Enrichment and removal of five brominated flame retardants in the presence of co-exposure in a soil-earthworm system. (1st October 2022) - Qiao, Zhihua; Lu, Cong; Han, Yanna; Luo, Kailun; Fu, Mengru; Zhou, Shanqi; Peng, Cheng; Zhang, Wei
Abstract: Brominated flame retardants (BFRs) are widely used because of their excellent flame retardant performance and are frequently detected in the soil environment. Their adverse impacts on soil organisms cannot be ignored. The enrichment and removal dynamics of the five BFRs (pentabromotoluene (PBT), hexabromobenzene (HBB), 1, 2-bis(2, 4, 6-tribromophenoxy) ethane (BTBPE), decabromodiphenyl ethane (DBDPE), and decabromodiphenyl ether (BDE209)) in earthworms and different tissues (epidermis, intestinal tract, and cast) in the presence of co-exposure were explored for the first time. The results showed that the enrichment of the five BFRs in earthworms increased with increasing exposure concentration and time. The distribution of these chemicals in different tissues of earthworms was different. The contents of HBB and PBT in the intestine and epidermis were the highest and were more than 60% during most of the time. Additionally, the contents of BTBPE, BDE209, and DBDPE were significantly increased while the contents of HBB and PBT were significantly decreased in the cast. The correlation analysis indicated that HBB and PBT had a significant relationship in all the tissues, but BDE209 and DBDPE only had a relationship in the cast, which might be attributed to the structure of the pollutants. Additionally, the experiments illustrated that earthworms had strong removal for HBB and PBT, but were weak for DBDPE and BDE209. Graphical abstract: Image 1 Highlights: Enrichment of five BFRs in epidermis and intestinal tract were different from cast. Similar enrichment and elimination patterns were observed for HBB and PBT. Enrichment capacity for HBB and PBT were greater than that of DBDPE and BDE-209.